PEMBELAJARAN KOMPETENSI MENULIS CERPEN MELALUI METODE SHOW NOT TELL - Abdul Azis; Mukhtar Mukhtar (STKIP Siliwangi, 2013)
This study aims to describe the application of the method show not tell in the process of learning to write short stories for the improvement of learning outcomes to write a short story using the Show Not Tell the students of class XI High School DDI Alliritengae Maros. This research is an action research conducted in two cycles. The data source of this research is an Indonesian teacher and students as many as 30 people. Data collection techniques used were observation and tests. The data in this study of the data and the data of the learning process of learning to write short stories using the Show Not Tell. Data were analyzed with the learning process qualitative descriptive techniques, while learning outcome data were analyzed with descriptive quantitative techniques. Learning outcomes through the method of writing short stories Show Not Tell in the first cycle reaches an average value of 59.17, while in the second cycle reached an average value of 80.37. Difference in the average value of 21.1 students. The average value of higher students in the second cycle than the first cycle, the results indicate an increase in learning to write short stories.Keywords: learning, writing, short stories, Show Not Tell.